The Effect of Free Time Management Skills upon Smartphone Addiction Risk in University Students - Deniz Mertkan Gezgin; Can Mihci; Sinem Gedik (Journal of Education in Science, Environment and Health)
The purpose of this study is to investigate the effect of free time management skills upon smartphone addiction risk in university students. The study follows a relational screening model of research and makes use of descriptive analyses alongside correlation and stepwise regression statistical methods. The study group consists of 591 university students. A glance at the findings indicate that the overall smartphone addiction risk in the study group is relatively low and that a statistically significant yet weak and negative relationship exists between smartphone addiction risk and free time management skills. Three out of the four sub-dimensions of free time management scale; namely "scheduling", "leisure attitude" and "goal setting" were found to be have statistically significant correlations with smartphone addiction risk at moderate, weak and weak levels respectively. Lastly, a stepwise regression test has shown that the "scheduling" sub-dimension alone is a significant predictor of smartphone addiction risk, explaining 15.2% of variance in scores. In conclusion, these findings may be interpreted as the possession of higher free time management skill in university students is associated with lower risk of smartphone addiction. The basis of this phenomenon may be inclination of some students to prefer spending all their free time using their smartphones, due to lack of management skills. The results have been further discussed further under the light of associated findings in the academic literature and implications for future research have been made.